2020
DOI: 10.1021/acsmacrolett.9b00895
|View full text |Cite
|
Sign up to set email alerts
|

One-Step and Metal-Free Synthesis of Triblock Quaterpolymers by Concurrent and Switchable Polymerization

Abstract: A one-step and metal-free route to triblock quaterpolymers from mixtures of vinyl monomers, epoxides, anhydrides, and racemic lactide (rac-LA) has been described, which bridges three polymerization cycles involving ring-opening copolymerization (ROCOP) of epoxides/anhydrides, ring-opening polymerization (ROP) of rac-LA, and RAFT polymerization of vinyl monomers. Taking advantage of the switchable polymerization between ROCOP and ROP, concurrent chain propagation of ROCOP/RAFT and ROP/RAFT sequentially occurs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 37 publications
0
59
0
Order By: Relevance
“…In view of the obvious correlation of PA and performance, this also seems a straightforward way to adapt the desired rate of polymerization by choice of catalyst according to PA. To the best of our knowledge, only a single example for a nitrogen base/borane catalyst setup targeting polymerization of epoxides has been published to date. 35 In a nal set of experiments, it was probed whether this userfriendly setup was also applicable to epoxides other than PO. Screening allyl glycidyl ether (AGE), tert-butyl glycidyl ether (tBuGE) and 1-butylene oxide (BO), it is found that these higher epoxide homologues entail a notable drop in speed of conversion while at the same time require a higher minimum PA of the applied organobase (Table S3 †).…”
Section: Resultsmentioning
confidence: 99%
“…In view of the obvious correlation of PA and performance, this also seems a straightforward way to adapt the desired rate of polymerization by choice of catalyst according to PA. To the best of our knowledge, only a single example for a nitrogen base/borane catalyst setup targeting polymerization of epoxides has been published to date. 35 In a nal set of experiments, it was probed whether this userfriendly setup was also applicable to epoxides other than PO. Screening allyl glycidyl ether (AGE), tert-butyl glycidyl ether (tBuGE) and 1-butylene oxide (BO), it is found that these higher epoxide homologues entail a notable drop in speed of conversion while at the same time require a higher minimum PA of the applied organobase (Table S3 †).…”
Section: Resultsmentioning
confidence: 99%
“…Bicomponent catalysts comprising Et 3 B/DBU Lewis acid/base pairs, reported by Wang et al, were also capable of switchable catalysis from mixtures of propylene oxide (PO), PA and LA yielding P(PO-alt-PA)-b-PLA. 19 By installing a functional chain end-group, RAFT polymerisation of methyl methacrylate formed PMMA-b-P(PO-alt-PA)-b-PLA. In this Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…14 The polymer is fully degradable and the monomers are (ε-decalactone (ε-DL)), or could be (cyclohexene oxide (CHO), phthalic anhydride (PA)), biobased. 14,19,20 Currently, the catalysts used to make these block polyesters through switchable catalysis display low turnover frequencies for at least one of the catalytic cycles. Here, this deficiency is tackled by the developing catalyst systems displaying high activities for both the ROP of ε-DL and ROCOP of PA with CHO.…”
Section: Introductionmentioning
confidence: 99%
“…The field of O-ATRP has proved to be one of the most successful modifications in devising a metal-free ATRP. The range of O-ATRP can be witnessed from its employment in synthesizing several versatile polymer structures, including the functionalization of various polymer chain ends, [94] polymer brush structures, [89] block, [95,96] multi-block, [97,98] and star polymeric structures. [99] The utilization of light enhances the control, leads to the removal of metal catalysts, and eventually benefits in extending this technique's applications.…”
Section: Synopsis and Outlookmentioning
confidence: 99%